In vitro and in vivo antibacterial activity of AM-833, a new quinolone derivative. - Hirai, K (1986)
AM-833 showed potent activity against members of the family Enterobacteriaceae, Neisseria spp., and Haemophilus influenzae and good activity against staphylococci, Pseudomonas aeruginosa, and Branhamella catarrhalis. Against these bacteria, its activity was roughly comparable to that of norfloxacin and ofloxacin but was slightly less potent than that of ciprofloxacin. This compound also showed good activity against drug-resistant strains such as methicillin-resistant Staphylococcus aureus and gentamicin-resistant Pseudomonas aeruginosa. The protective effects of a single oral dose of AM-833 on systemic bacterial infections in mice were greater than those of norfloxacin. AM-833 was as effective as ofloxacin and ciprofloxacin against systemic infections with Escherichia coli and Pseudomonas aeruginosa, and it showed somewhat higher activity against staphylococcal infections than did the other quinolones. AM-833 exhibited good prophylactic activity against E. coli infections. AM-833 also proved effective against localized infections such acute pneumonia and ascending urinary tract infections in mice. The excellent therapeutic efficacy of AM-833 against these systemic and local infections may be a result of its good oral absorption and high levels in tissues.